Systematic Literature Riview: Manfaat E-Modul Interaktif untuk memfasilitasi Pembelajaran Matematika Siswa dalam Menyelesaikan Masalah - Destha Ulandari; Khathibul Umam Zaid Nugroho; As Elly (Proceeding of Silampari Conference of Life Science and Technology, 2026)
This research is motivated by the importance of using innovative learning media to facilitate students’ mathematics learning in solving problems. One of the learning media that can be used is an interactive e-module, which is able to create a more interesting, active, and independent learning process through the use of digital technology. This study aims to determine the benefits of interactive e-modules in facilitating students’ mathematics learning in problem solving and to identify the characteristics of interactive e-modules in mathematics learning. The research method used in this study is a Systematic Literature Review (SLR). Data collection was carried out through several stages, namely research question, selection criteria, develop search strategy, select studies, the quality of studies, and synthesis result related to learning models using interactive e-modules that are relevant to this research. This study employed PICCOC analysis (Population, Intervention, Comparison, Outcome, and Context). The reviewed articles consisted of 14 articles that met the inclusion and exclusion criteria out of a total of 47 articles. The sources of information used in this study were obtained from Publish or Perish, Google, and Google Scholar. Based on the results of the review of the 14 selected articles, it can be concluded that the development and implementation of interactive e-modules have a positive impact on improving students’ learning outcomes. In addition, interactive e-modules are also able to enhance students’ problem-solving skills, mathematical understanding, mathematical reasoning, and mathematical communication skills, especially in mathematics learning.